Static light scattering of concentrated particle systems in the Rayleigh-Debye-Gans regime: Modeling and data analysis - Elicabe, Guillermo Enrique (2010)
In this work we give an overview of the Rayleigh-Debye-Gans (RDG) theory applied to the analysis of static light scattering (SLS) data of different types of concentrated particle systems. First some useful models needed to analyze SLS data under the RDG regime for concentrated particle systems are presented. We consider monodisperse as well as polydisperse systems of spherical particles. Then we present some techniques for analyzing the SLS data in different contexts with the aim of gathering information about: particle size and shape, particle size distribution, particle concentration, and some other useful parameters characterizing the particle systems. Finally, we report an application of some of the models and methods illustrated previously. They were used to characterize a system of concentrated polymer particles embedded in a polymer matrix, formed as the result of a phase separation induced by polymerization in a polymer blend.